1990
DOI: 10.2466/pms.1990.71.3.723
|View full text |Cite
|
Sign up to set email alerts
|

Field Dependence and Body Balance

Abstract: This study reports four points about the portable Rod and Frame Test performance of 30 Japanese women in terms of body balance. The primary findings using a stabilometer are: (a) field dependence correlated negatively with increased sway path within 1 min. both while a dot pattern as a visual stimulus was stationary and while it was moving. (b) Field dependence correlated positively with the difference in sway path between the two following phases, in one of which the subjects watched the horizontal visual mov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 12 publications
1
4
1
Order By: Relevance
“…IOtamura and Matsunga (19) found that women and elderly people have an increased score on visual field dependence; however, the equal distribution of subjects across groups by age and sex in our experiments rules out an interpretation of our results by these factors. Evaluations of the subjective vertical have been previously reported in Parkinson's disease patients, but the results are inconsistent from one study to another.…”
Section: Discussioncontrasting
confidence: 73%
“…IOtamura and Matsunga (19) found that women and elderly people have an increased score on visual field dependence; however, the equal distribution of subjects across groups by age and sex in our experiments rules out an interpretation of our results by these factors. Evaluations of the subjective vertical have been previously reported in Parkinson's disease patients, but the results are inconsistent from one study to another.…”
Section: Discussioncontrasting
confidence: 73%
“…The visual field dependence-independence thus appears to be a good predictor of the subject's global ability to stabilise both the head and whole body efficiently. Similar but smaller differences between FD and FI subjects were previously found in women standing with the feet together, suggesting that these differences may be task-and/or sex-dependent (Kitamura and Matsunaga 1990).…”
Section: Discussionsupporting
confidence: 58%
“…It is well known that motor action and depth vision are linked (Wexler & van Boxtel, 2005) and that some participants rely more on visual cues to control balance than others (Kitamura & Matsunaga, 1990). Participants with an increased dependence on visual field information (FD) are characterized as less physically stable and more reliant on visual cues (particularly motion visual cues) for controlling body stabilization.…”
Section: Visual Dependence and Motionmentioning
confidence: 99%